Sea ice dynamics influence halogen deposition to Svalbard - Spolaor, Andrea; GABRIELI, Jacopo; VARIN, Cristiano; VALLELONGA, PAUL TRAVIS; BARBANTE, Carlo; Martma, T.; Kohler, J.; Björkman, M. B.; Isaksson, E.; Plane, J. M. C. (The Cryosphere, 2013)
Sea ice is an important parameter in the climate system and its changes impact upon the polar albedo and at- mospheric and oceanic circulation. Iodine (I) and bromine (Br) have been measured in a shallow firn core drilled at the summit of the Holtedahlfonna glacier (Northwest Spitsber- gen, Svalbard). Changing I concentrations can be linked to the March–May maximum sea ice extension. Bromine en- richment, indexed to the Br / Na sea water mass ratio, appears to be influenced by changes in the seasonal sea ice area. I is emitted from marine biota and so the retreat of March–May sea ice coincides with enlargement of the open-ocean surface which enhances marine primary production and consequent I emission. The observed Br enrichment could be explained by greater Br emissions during the Br explosions that have been observed to occur mainly above first year sea ice during the early springtime. In this work we present the first compari- son between halogens in surface snow and Arctic sea ice ex- tension. Although further investigation is required to charac- terize potential depositional and post-depositional processes, these preliminary findings suggest that I and Br can be linked to variability in the spring maximum sea ice extension and seasonal sea ice surface area.